2012
DOI: 10.1186/1748-5908-7-34
|View full text |Cite
|
Sign up to set email alerts
|

Trust, confidentiality, and the acceptability of sharing HIV-related patient data: lessons learned from a mixed methods study about Health Information Exchanges

Abstract: BackgroundConcerns about the confidentiality of personal health information have been identified as a potential obstacle to implementation of Health Information Exchanges (HIEs). Considering the stigma and confidentiality issues historically associated with human immunodeficiency virus (HIV) disease, we examine how trust—in technology, processes, and people—influenced the acceptability of data sharing among stakeholders prior to implementation of six HIEs intended to improve HIV care in parts of the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…This was consistent with studies that have found that PLWH were willing to share PHI with essential need-to-know clinicians (Maiorana et al, 2012; Patel et al, 2011; Teixeira, Gordon, Camhi, & Bakken, 2011). On the other hand, the fact that almost 48% of PLWH in this HIV clinic had neither consented nor declined represented a missed opportunity to improve quality of care and quality of life for PLWH, given the evidence of the importance of sharing PHI across providers to support the HIV care continuum (Mugavero, Amico, Horn, & Thompson, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…This was consistent with studies that have found that PLWH were willing to share PHI with essential need-to-know clinicians (Maiorana et al, 2012; Patel et al, 2011; Teixeira, Gordon, Camhi, & Bakken, 2011). On the other hand, the fact that almost 48% of PLWH in this HIV clinic had neither consented nor declined represented a missed opportunity to improve quality of care and quality of life for PLWH, given the evidence of the importance of sharing PHI across providers to support the HIV care continuum (Mugavero, Amico, Horn, & Thompson, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…In planning for an opt-out model, Hunter, Haining and Whiddett conducted a survey where 39% of patients expressed that they wanted more information, prior discussion or consent before they felt comfortable with their sexual health service records being integrated with EHR 23. This has been echoed in another study where clients’ acceptability of sharing electronic health information was dependent on building trust in providers and institutions prior to EHR implementation 28. Similarly, the results from our study suggest that careful planning to address patient privacy concerns and evaluation of the impacts should be conducted during the implementation and use of EHR.…”
Section: Discussionmentioning
confidence: 99%
“…Maiorana et al (2012) illustrate this approach in their study about trust and acceptability of sharing HIV-related patient data. Quantitative survey data with HIV patients and qualitative interview data with medical staff were merged for comparison, using the qualitative findings to provide a more in-depth understanding of the quantitative drivers and barriers of sharing HIV-related patient data (Maiorana et al, 2012). The quantitative data framed the analysis and the qualitative data were used to elaborate and explain the quantitative findings.…”
Section: Explanatory Unidirectional Framework For Data Merging Analyticsmentioning
confidence: 99%
“…We were less successful in identifying studies using either the explanatory bidirectional or exploratory bidirectional framework. We suspect this is at least partly attributable to the practice of authors truncating discussion in the methods and instead allocating words to the results or discussion section due to word count restrictions.Very few studies we identified were explicit about the drivers of the analysis (Maiorana et al, 2012; Myers et al, 2012), making it difficult not only to systematically search and review the MMR literature but also to identify the analytical framework used in the integration of quantitative and qualitative data. Several reviews have found that most MMR papers lack clarity in whether the reported results stem from…”
mentioning
confidence: 99%